EDUKASI HUKUM TENTANG PERJANJIAN BAKU DALAM JUAL BELI DAN PINJAMAN ONLINE BAGI IBU-IBU PKK RW 01 JL. MAKMUR, KELURAHAN HARAPAN MULYA, KECAMATAN MEDAN SATRIA, KOTA BEKASI. - Mestika Mentari Magenta; Putri Nadia; Ika Dewi Sartika Saimima (Abdi Bhara, 2023)
The development of information technology also has animpact on the economic sector, as a result of which there arecompanies in the e-commerce business and non-banking financecompanies that develop their business based on technology andthe internet. The method used in this community service activityis carried out by providing socialization and counseling toFamily Welfare Movement in RW 01 Harapan Mulya Village,Medan Satria District, Bekasi City. This community serviceactivity is carried out by referring to the Civil Code andFinancial Services Authority Regulation Number77/POJK.01/2016 concerning Information Technology-BasedMoney Lending Services. The purpose of this community serviceactivity is to provide legal education about buying and sellingactivities and the existence of Fintech financial services. FamilyWelfare Movement were introduced to the existence of standardagreements in e-commerce agreements and online loanagreements. This community service activity explains a billingsystem that is in accordance with norms and decency, protectionof consumers' personal data, and accommodates developmentsand economic relations between Fintech companies andconsumers.